Peri-operative Care for Suspected or Confirmed COVID-19 Cases: A major Concern for the Public Health: A Review Article - Vanthichal, Krishnaprasad Gopalkrishna; Ray, Arijit; Paul, Debashish (Journal Of Nursing Practice, 2020)
Background: Personal Protective Equipment (PPE) including gown, shoe cover, face mask, eye goggles, cap, face shield and gloves for health-care professional in operation theatre is a must in order to contain COVID-19 pandemic. It is imperative to mention that a surgical patient whether suspected or confirmed cases of COVID-19 must receive peri-operative care as it is the mainstay in care of surgical patient which cannot be denied to anyone. If we look at the incidences and the trend of spreading the COVID-19 infection, any breech in the personal and professional preventive steps to this infection in peri-operative care imposes greater risk to the public health as it affects the health care workers. Anesthetisologist and other staffs and health care workers (HCWs) in the operating room are in close proximity to patients. They are always in events of increased aerosol production from an infected patients, whether it is intubation, Bag and mask Ventilation or suctioning of the airway and life saving procedures.The major route of spread is contact transmission.Cross-infection is the major hindrance to seamless healthcare service to Covid-19 patients. Hand-washing is the universal viral transmission containment step. But it will not suffice to the preventive goal of these HCWs. Though operation rooms are maintained with negative pressure atmosphere which is ideal to minimize infection risk but this is the time to rehearse and practice other aspects too.Conclusion: The peri-operative care providers’ face several challenges in operation theatre and during per-operative care while treating suspected or confirmed cases of COVID-19 and thus pose a greater risk to the society. We tried to summarise these vital points and practices, dissemination of which is of utmost importance at this pandenmic scenario.